The Use of Proton Pump Inhibitors and Prescription Pattern by Practicing Physicians at an Academic Hospital - Mohammed A. Basheikh, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The introduction of proton pump inhibitors has revolutionized the management of acid-related gastrointestinal disorders. Physicians use different regimen when prescribing proton pump inhibitors. In this study we aim to determine the prevalence and pattern of proton pump inhibitors prescription among practicing physicians at King Abdulaziz University Hospital in Jeddah, Saudi Arabia. A cross-sectional study was performed at different levels of doctors ranging from consultants to house officers from March-May 2014. The study included 85 doctors. The prevalence of proton pump inhibitors prescription was 57.65%. Most of the respondents are internal medicine physicians with 58.62% (29 physicians) of them prescribing proton pump inhibitors. As well, half of the surgeons (24) were prescribing proton pump inhibitors. 54.17% of house officers who participated were prescribing proton pump inhibitors. Omeprazole at a dose of 20 mg is the most commonly prescribed by 49.41%, followed by the dose 40 mg prescribed by 41.18%. The rate of prescription for proton pump inhibitors at King Abdulaziz University Hospital with different specialties and levels is comparable to the practice worldwide. It’s noted that house officers are prescribing proton pump inhibitors; they will need to be educated about the use, dosage, and side effects of proton pump inhibitors.